Urban China’s Long-Term Care Landscape: A Narrative Review of Current Practices and Emerging Trends (Bangladesh Journal of Medical Science, 2026)
Background As a consequence of the One-child Policy (1979–2015), China is confronting a rapidly aging population 1. This demographic transition imposes significant pressure on the existing long-term care (LTC) system, which remains inadequate in addressing the escalating demand. Consequently, there is an urgent imperative to develop a more efficient and sustainable LTC model. This literature review examines recent practices and innovative advancements within the LTC system in urban China Design and methods This narrative literature review employed an iterative search approach to identify relevant literature and key subtopics. A total of 257 articles met the inclusion criteria, all of which were reviewed. The findings were analyzed and compared across the selected studies. Results This review analyzed 81 studies, 50 in English and 31 in Chinese. The findings highlight several critical challenges facing China, including demographic aging, shrinking family sizes, a rising elderly dependency ratio, caregiver shortages, and concerns over financial sustainability. Published literature emphases key emerging trends, including the growth of home- and communitybased care (HCBC), healthcare–LTC integration, and innovative models like smart LTC and time banks to alleviate workforce and resource pressures. Conclusions In response to profound demographic shifts, China’s LTC landscape is undergoing a transformation from traditional family-based care to publicly supported long-term care services. This transition has spurred rapid development of HCBC, positioning it as a cornerstone for aging in place model. Moving forward, establishing an LTC model that is both efficient and sustainable will be essential to meeting the diverse and growing needs of China’s aging population.BJMS, Vol. 25 No. 02 April’26 Page: 436-445